Allocation of goods through non-price mechanisms: evidence on distribution by willingness to wait - Alderman, Harold (Elsevier, 1987)
This paper discusses a model of market clearing when prices are rigid. The estimated model is one in which the waiting time necessary to obtain the scarce goods brings the excess demand in line with current supply in a manner of a flexible price. The mechanism of such a market has been discussed by Barzel and by Nichols, Smolensky and Tideman, but little empirical evidence has been reported. Estimation of consumer demand in such a market is presented here. Heckman's approach to truncated sample estimation has been employed. The approach allows modelling of time costs as a two-part tariff. The results confirm that consumer's response to waiting time is measurable and in the same order of magnitude as expected from response to changes in prices. The study also indicates that rationing by willingness to wait does not necessarily distribute goods to the poor.